2020
DOI: 10.21511/ppm.18(2).2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Chinese high-tech foreign direct investments in the EU – trends and policy responses

Abstract: This paper aims to examine the trends of Chinese high-tech acquisitions in the EU countries, describe the policies that these acquisitions prompted on the level of member states and the EU, and analyze the effects of these policy responses. The results of the research review clearly show an increasing number of takeovers of European companies in the high-tech sectors, especially in the big member states such as Germany, France, or the UK. This created a backlash from the European policymakers that led to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Risk response, RM, and performance were not significantly affected by HRs in hazard RM. As Dudas and Rajnoha [73] found, the possibility of withdrawal has a positive impact on rather than the management of risk, as indicated by this study. The market condition in the host country disappears if tax laws and regulations frequently change, subsidiaries have an advantage in local management, and the environment degrades [7,74].…”
Section: Efficiency-seekingsupporting
confidence: 70%
See 3 more Smart Citations
“…Risk response, RM, and performance were not significantly affected by HRs in hazard RM. As Dudas and Rajnoha [73] found, the possibility of withdrawal has a positive impact on rather than the management of risk, as indicated by this study. The market condition in the host country disappears if tax laws and regulations frequently change, subsidiaries have an advantage in local management, and the environment degrades [7,74].…”
Section: Efficiency-seekingsupporting
confidence: 70%
“…Companies seeking market share would not withdraw subcontractors or give up business from a large company. However, efficiency-seeking companies would withdraw operations from China or reverse their decision to return to foreign operations because tariffs on these components can increase production costs [73,74]. It has also been found that those businesses that pursued differentiation strategies (strengthening brands, quality, and customer service) had the most significant impact.…”
Section: Mediating Effects Of Investment Motivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese investment of $250m to date is still relatively modest but reflects risks for investments in Ukraine, rather than lack of interest (Malyarenko & Wolff, 2021). Additionally, certain Chinese investments fall in the context of government-coordinated policies of the acquisition of high-tech companies (Dudas & Rajnoha, 2020). At least some Ukrainian doublepurpose and military technologies are within the Chinese interest.…”
Section: Ukraine and Shifting Great Power Dynamicsmentioning
confidence: 99%